Hibridismo cultural na Amazônia brasileira: um estudo do romance "Cinzas do Norte", de Milton Hatoum - Lorena de Carvalho Penalva (2015)
Throughout this thesis we aim to examine the processes of construction of cultural identity in the Brazilian Amazon, from the novel Ashes of the Amazon (2005) by Milton Hatoum. Therefore we discussed the geographical, cultural, economic and literary aspects of the Amazon region, as well as studies on the concepts of hybridity, cultural difference and rhizome, and analysis of hatouniana fiction. As a result, assuming the existence of a fictional representation of the Amazon tradition, which began with the report of the first travelers, the work of Milton Hatoum was constructed from flexible assumptions and heterogeneity in the trajectory of the characters, especially the World serving as a conductor of the narrative axis. Accordingly, we have analyzed the work of the Amazon Hatoum pictures by the artistic vision of specific characters, including contradiction between modernity and modernization in Manaus, and the displacement and errors in the world that destabilize the local / global ideas and the narrative configurations of Hatoum. This proposal is theoretically based on the author's cultural studies and contemporary post-structuralism criticism, as Bhabha Hall, Canclini, Derrida, Deleuze and Guattari; we believe that this critical research was developed in order to deconstruct, or rather destabilize hegemonic values and Western archetypes.